Transforming growth factor-β in tumour development - Trelford, Charles B.; Dagnino, Lina; Di Guglielmo, Gianni M. (Frontiers in Molecular Biosciences, 2022)
Transforming growth factor-beta (TGFβ) is a ubiquitous cytokine essential for embryonic development and postnatal tissue homeostasis. TGFβ signalling regulates several biological processes including cell growth, proliferation, apoptosis, immune function, and tissue repair following injury. Aberrant TGFβ signalling has been implicated in tumour progression and metastasis. Tumour cells, in conjunction with their microenvironment, may augment tumourigenesis using TGF to induce epithelial-mesenchymal transition, angiogenesis, lymphangiogenesis, immune suppression, and autophagy. Here, we review TGFβ signalling pathways, the biology of TGFβ during tumourigenesis, and how protein quality control pathways contribute to the tumour-promoting outcomes of TGF signalling.